Information and Computer Literacy - Marcen, Benjamin (Interdisciplinarna in uporabna znanja za zelene in digitalne logistične procese, 2025)
In today's digitalised world, information literacy is a key skill that enables the effective and confident use of technology. In this chapter we will explore all aspects of information and computer literacy that are indispensable for the modern individual. We will start with basic steps such as using and customising the desktop, working with the taskbar and icons, and managing files and folders. We will also learn how to use explorer, lock and compress files and manage various useful applications. We will continue with more advanced use of Word and Excel. We will look in detail at creating and formatting text, using cross-references, creating tables, using functions and entering graphs. In addition, we will explore user communication. The use of different internet browsers and online communication applications such as Microsoft Teams and Zoom. The aim of this chapter is to provide you with a solid foundation for confident and effective use of the digital tools and applications that are essential for success in today's technologically advanced world.